Kesabaran dalam Perspektif Hadis Tarbawi - Nurfadillah Nurfadillah; Sri Wahyuni; Ummiati Anshari Purba; Dwi Meutia Hasni (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The concept of patience (sabr) occupies a fundamental position in Islamic teachings and constitutes an essential moral value for both educators and students. This study aims to analyze the concept of patience from the perspective of hadith and to explain its relevance in Islamic education, particularly in character development. This research employs a qualitative approach with a library research design. Primary data were obtained from hadiths contained in the Kutub al-Sittah, while secondary data were drawn from Islamic education literature. Data were analyzed using content analysis with a thematic approach. The findings reveal that, from the hadith perspective, patience is not merely a passive attitude of suppressing emotions, but rather an active inner strength that encompasses steadfastness in obedience, avoidance of prohibitions, and resilience in facing trials. In the context of learning, patience serves as a foundation that fosters sincere intention, a growth mindset, and perseverance in the pursuit of knowledge. For educators, patience is an essential character trait for guiding students with gentleness and exemplary conduct without coercion, as demonstrated by the Prophet Muhammad ﷺ in his treatment of Tsumamah bin Utsal. The implications of this study affirm that the systematic internalization of the value of patience in Islamic education significantly contributes to the development of students who are resilient, disciplined, and mentally strong in facing academic and social challenges.